Identification and characterization of pathogenic Aeromonas sp isolated from clinically diseased rainbow trout (Oncorhynchus mykiss) raised in Peruvian fish farms - Nuñure O., Jeferson (2021)
The present research aimed at the biochemical characterization and molecular identification of pathogenic strains of Aeromonas sp, isolated from juvenile rainbow trout with clinical signs compatible with aeromoniasis in six fish farms in Junín (2), Pasco (2), Cajamarca (1) and Ancash (1), Peru. In total, 60 juvenile trout of 4-5 months were selected, with suggestive signs of outbreaks of aeromoniasis between 2017 and 2018. Euthanasia and necropsy were performed and the external and internal lesions present were recorded. Bacterial isolation of spleen and anterior kidney samples was carried out on TSA and GSP agar for 24-48 hours at 25 °C, bacterial colonies were characterized by biochemical tests and identified by conventional PCR using specific primers of the 16S rRNA gene (Aeromonas spp.), fstA (A. salmonicida) and gyrB (A. hydrophila), and sequencing was performed and confirmed by BLAST analysis (NCBI). The external lesions were melanosis, necrotic and haemorrhagic fins, skin ulcers and abdominal distention. Internal lesions were hepatomegaly, splenomegaly, and petechial haemorrhage in the liver, pyloric cecum, and peritoneal fat. Twelve strains were isolated in GSP (7 from Junín and 5 from Cajamarca), characterized as Aeromonas spp, being negative in the Pasco and Ancash samples. The biochemical tests determined four strains as Aeromonas salmonicida and eight as mobile Aeromonas sp, differing by motility and indole tests. Molecular identification by PCR determined four A. salmonicida strains from Junín, one A. hydrophila strain from Cajamarca and seven Aeromonas spp mobile strains (3 from Junín and 4 from Cajamarca) that were negative to the PCR of A. salmonicida and A. hydrophila. BLAST analysis (NCBI) confirmed the strains A. salmonicida and Aeromonas spp (98-100% identity). Furthermore, the Cajamarca strain (identified as A. hydrophila by biochemistry) presented 95.65% identity with A. hydrophila subspecies dhakensis. In conclusion, Aeromonas salmonicida, A. hydrophila subspecies dhakensis and other pathogenic mobile Aeromonas produce symptoms associated with aeromoniasis in juvenile rainbow trout in the Junín and Cajamarca fish farms. It is the first time that A. hydrophila subsp. dhakensis is detected in the country.